Padrão de sensibilidade de cepas de Enterobacter spp isoladas na região de Presidente Prudente - SP - Braoios, Alexandre; Grigoli, Vanessa Lopes; Bellini, Camila Aparecida; Almeida, Mércia de Carvalho; Pizzolitto, Antonio Carlos [UNESP] (My University, 2002)
Enterobacter spp. are considered important causing agents of infection, specially in hospitalized individuals. The natural resistance of these microorganisms and the great facility to develop resistance to new antimicrobial agents make this genus an important object of study. In this work, 176 strains isolated from various clinical samples were used from hospitalized patients (University Hospital Domingos Leonardo Cerávolo) and from clinic patients (Clinical Laboratory from Unoeste), both situated in Presidente Prudente - SP. E. cloacae (78.9%), E. aerogenes (7.9%) and E. (pantoea) agglomerans (3.9%) were the ones more frequently isolated. Eleven antimicrobial agents were tested by the disk diffusion method and around 90% of the strains presented resistance to the cephalotin, ampicillin and cefaclor. Strains of E. (pantoea) agglomerans presented wide profile of sensibility However one strain of E. cloacae presented resistance to all the antimicrobial agents. The antimicrobial agents with greater inhibitory activity were imipenem and cefepime, for this reason these antimicrobial agents could be the treatment of choice in emergencial therapeutic. This emergencial therapy can be applied with relative security, whereas the data obtained in this study show homogeneity in the profile of sensibility to these antimicrobial agents, independent of the infection site and from the isolated species. The ESBL enzyme could not be detected in no one of the strains by the double diffusion test.
Sensibility profile of strains of Enterobacter spp isolated in the region from Presidente Prudente - SP
Keywords: Antimicrobial agents; Antimicrobial resistance; Enterobacter; Profile of sensibility; ampicillin; cefaclor; cefalotin; cefepime; cefotaxime; chloramphenicol; ciprofloxacin; gentamicin; imipenem; tetracycline; antibiotic resistance; bacterial strain; bacterium isolation; controlled study; diffusion; Enterobacter aerogenes; Enterobacter cloacae; hospital infection; human; major clinical study; minimum inhibitory concentration; nonhuman; Pantoea agglomerans